New fundamentals in hemostasis - Versteeg, Henri H; Heemskerk, Johan W M; Levi, Marcel; Reitsma, Pieter H (Physiological reviews, 2013)
Hemostasis encompasses the tightly regulated processes of blood clotting, platelet activation, and vascular repair. After wounding, the hemostatic system engages a plethora of vascular and extravascular receptors that act in concert with blood components to seal off the damage inflicted to the vasculature and the surrounding tissue. The first important component that contributes to hemostasis is the coagulation system, while the second important component starts with platelet activation, which not only contributes to the hemostatic plug, but also accelerates the coagulation system. Eventually, coagulation and platelet activation are switched off by blood-borne inhibitors and proteolytic feedback loops. This review summarizes new concepts of activation of proteases that regulate coagulation and anticoagulation, to give rise to transient thrombin generation and fibrin clot formation. It further speculates on the (patho)physiological roles of intra- and extravascular receptors that operate in response to these proteases. Furthermore, this review provides a new framework for understanding how signaling and adhesive interactions between endothelial cells, leukocytes, and platelets can regulate thrombus formation and modulate the coagulation process. Now that the key molecular players of coagulation and platelet activation have become clear, and their complex interactions with the vessel wall have been mapped out, we can also better speculate on the causes of thrombosis-related angiopathies.